Penerapan Restorative Justice Berbasis Nilai Kearifan Lokal - Rahman, Malik Mulyanto; Syahrul, Syahrul; Moonti, Roy Marthen; Kasim, Muslim A. (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Handling of child cases in Eastern Indonesia faces various challenges, ranging from limited legal infrastructure to the strong influence of local culture. This study evaluates the application of a restorative justice approach that integrates local wisdom values in resolving child cases, with a focus on the socio-cultural context of the community in the region. Through qualitative methods with case studies in several regions in Eastern Indonesia, this study reveals that a restorative approach based on custom and deliberation has proven to be more effective in restoring social harmony, preventing stigmatization of children, and encouraging rehabilitation compared to a formal litigation approach. The findings also show that the involvement of traditional figures, families, and local communities is key to the success of the restorative justice process. However, challenges remain in terms of regulation and uniformity of understanding among law enforcement officers. This study recommends the need for synergy between the national legal system and local wisdom to create a more contextual, inclusive, and equitable model for handling child cases.